Performance Of Village Apparatus In Minimizing Poverty Through Food And Animal Security Work Program In Tompo Village, Barru District, Barru Regency - Marsuki, Marsuki; Aidah, Aidah (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to determine the performance of village officials in minimizing poverty through food and animal security work programs in Tompo Village, Barru District, Barru Regency, as well as to identify factors that affect the performance of village officials in minimizing poverty through the program. Data sources are obtained through surveys, interviews, observations, and documentation. The results of the study show that the performance of village officials in minimizing poverty in Tompo Village is good. This research is based on four indicators, namely facilities and infrastructure, methods, human resource capabilities, and work morale. The factors that hinder the performance of village officials in minimizing poverty in Tompo Village are limited budget, the ability of the community to manage cattle, and difficulties in obtaining cow broodstock.